2010
DOI: 10.1073/pnas.1001165107
|View full text |Cite
|
Sign up to set email alerts
|

The G protein-coupled receptor T-cell death-associated gene 8 (TDAG8) facilitates tumor development by serving as an extracellular pH sensor

Abstract: Tumors often are associated with a low extracellular pH, which induces a variety of cellular events. However, the mechanisms by which tumor cells recognize and react to the acidic environment have not been fully elucidated. T-cell death-associated gene 8 (TDAG8) is an extracellular pH-sensing G protein-coupled receptor that is overexpressed in various tumors and tumor cell lines. In this report, we show that TDAG8 on the surface of tumor cells facilitates tumor development by sensing the acidic environment. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 46 publications
4
62
0
Order By: Relevance
“…7D). This follows from previous work by other groups demonstrating that pH-activated GPR65 signals through the G␣ s /cAMP pathway and additionally through ERK1/2 phosphorylation (22,23,25). The ablation of both downstream signals indicates that our knockdown protocol effectively blunts the activity of GPR65.…”
Section: Acidosis-induced Elevation Of Bcl-2 and Bcl-xl Occurs Throughsupporting
confidence: 57%
See 1 more Smart Citation
“…7D). This follows from previous work by other groups demonstrating that pH-activated GPR65 signals through the G␣ s /cAMP pathway and additionally through ERK1/2 phosphorylation (22,23,25). The ablation of both downstream signals indicates that our knockdown protocol effectively blunts the activity of GPR65.…”
Section: Acidosis-induced Elevation Of Bcl-2 and Bcl-xl Occurs Throughsupporting
confidence: 57%
“…The activation of GPR65 only occurs below pH 7.4 and reaches maximal activity between pH 6.2 and 6.8, in line with in vivo tumor pH (22,23). Additionally, it was recently revealed that the ability of GPR65 to promote tumor formation requires its acid-sensing capabilities (25). Whereas these reports provide evidence for the importance of GPR65 in cancer, exactly how the receptor exerts its oncogenic function is unknown.…”
mentioning
confidence: 88%
“…Our interest in elucidating a role for an acid sensor in the kidney has been based on the relatively high expression of the proton-sensing receptor GPR4 in the kidney and the responses of other members of the proton-sensing family of GPCR to a decrease in pH in various tissues [e.g., OGR1 in bone (36,37,55) and lung], TDAG8 in lung carcinoma (50), and GPR4 in blood vessels (106). We found that the deletion of GPR4 impairs net acid excretion in the kidney, and therefore a spontaneous non-gap metabolic acidosis develops (88).…”
Section: Discussionmentioning
confidence: 99%
“…99 Another group demonstrated in NCI-H460 human non-small cell lung cancer cells that GPR65 promotes cancer cell survival in an acidic microenvironment. 100 Conversely, a recent study showed that GPR65 inhibited c-Myc oncogene expression in human lymphoma cells. 101 Furthermore, GPR65 messenger ribonucleic acid expression was reduced by more than 50% in a variety of human lymphoma samples when compared to normal lymphoid tissues, therefore implying GPR65 has a tumor suppressor function in lymphoma.…”
mentioning
confidence: 99%